COPING STRATEGIES AMONG KINDERGARTENERS IN THE GENDER PERSPECTIVE - Muthmainah Muthmainah; Edi Purwanta; Suwarjo Suwarjo; Mariani Binti Md Nor (LPMPP Universitas Negeri Yogyakarta, 2021)
Negative emotions remains common among some kindergarteners in general since it may impact their anxiety and stress. This study aimed to describe various elicitors for negative emotions among young children, their coping strategies, and the parents’ response to them in the gender perspective. The data were collected through questionnaires containing statements about coping strategies of their children developed using the Lazarus and Folkman theories and findings by Chalmers, Frydenberg, and Deans. The study involved 102 parents of children aged 4-6 years in Yogyakarta, Indonesia. The findings show that elicitors for negative emotions among boys are dominated by physical bullying by peers, while in girls, they are dominated by unfulfilled wishes. Meanwhile, coping uses among boys are dominated by assertive behavior, while in girls, they share their concerns with others. Regarding the response in dealing with children’s negative emotions, the parents give them a gadget, such as smartphone, for both boys and girls. The study implies that more educational parenting model is needed to educate parents in handling negative emotions through coping skills and indiscriminating behavior.